New species of Hemileucoglossum (Geoglossaceae, Geoglossales, Geoglossomycetes) from Southwest China - Wu, Ting; Yu, Feng-Ming; Zhao, Qi (Phytotaxa, 2026)
The earth tongues genus Hemileucoglossum represents a small group within the family Geoglossaceae, which remains poorly studied due to its uncommon occurrence. This genus can be distinguished from other genera of the family by its non-viscid ascomata, the absence of setae in the hymenium, the presence of setose hairs on the stipe, and ascospores that are hyaline to moderately pigmented at maturity. Although this genus is widely distributed globally, it has not been recorded in China. During an investigation of the earth tongues species in the Gaoligong Mountains of Yunnan, Southwest China, a new species of Hemileucoglossum was discovered. The species, H. yunnanense, is characterized by the small, entirely black and capitate ascomata, a relatively scaly stipe (especially in the upper part), and hyaline ascospores with a variable number of septa (predominantly 0-1-2-6-7-septa, less frequently 3-5-10-septa, and occasionally more than 10 septa). It was found growing in a subtropical area at an elevation of 2,743 m. The status of H. yunnanense as a new species is supported by both morphological examination and molecular phylogenetic analysis based on the internal transcribed spacer (ITS) region and the portion of nuclear large subunit ribosomal DNA (LSU). In this paper, we provide a detailed description with photographs for this species.